The Effect of Transformational Leadership, Workload, Work Engagement on Emotional Exhaustion and Organizational Citizenship Behavior at PT. Wangta Agung Surabaya - Wiwit Lusiana; Slamet Riyadi; Sumiati Sumiati (International Journal Labs, 2025)
The problem of organizational citizenship behavior has not been fully implemented among employees. Employees are not willing to carry out more than their main duties and have not provided more than expected capabilities to the organization to improve the effectiveness of the company. The purpose of this study is to determine the influence of transformational leadership, workload and work engagement on emotional exhaustion and organizational citizenship behavior of employees at PT. Wangta Agung Surabaya. This study was carried out by a quantitative method supported by primary data sources obtained through the distribution of questionnaires. The research population is employees of PT. Wangta Agung Surabaya. The selection of respondents was carried out by the saturated non-probability sampling method with a total of 102 respondents. The method of analyzing the data is by descriptive analysis and SEM-PLS analysis. The findings of the study show that transformational leadership and workload have a significant effect on emotional exhaustion and organizational citizenship behavior of employees at PT. Wangta Agung Surabaya, while work engagement has a non-significant effect on emotional exhaustion but work engagement has a significant influence on OCB at PT. Wangta Agung Surabaya.